2008
DOI: 10.1148/radiol.2482071674
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed High-Intensity Focused Ultrasound Enhances Apoptosis and Growth Inhibition of Squamous Cell Carcinoma Xenografts with Proteasome Inhibitor Bortezomib

Abstract: Purpose: To investigate whether combining pulsed high-intensity focused ultrasound (HIFU) with the chemotherapeutic drug bortezomib could improve antitumor activity against murine squamous cell carcinoma (SCC) tumors. Materials and Methods: All experiments were conducted with animal care and use committee approval. Murine SCC cells were implanted subcutaneously in C3H mice. When tumors reached 100 mm3, mice were randomized to one of three groups for twice weekly intraperitoneal injections of 1.5 mg of bortez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 26 publications
6
55
0
Order By: Relevance
“…16 At present, palliative chemotherapy remains the main therapeutic approach used to treat advanced gastric cancer, but the response rates to combined chemotherapy range from approximately 26% to 47.9%. 13,17,18 In this study, 185 patients were subjected to 5-fluorouracil-based chemotherapy and the objective response rate of group A was 34.3%, which was similar to that in a previous study. 19 With the high incidence of lymph node metastasis and the lack of effective therapies, HIFU has been considered a strong candidate for treatment combined with chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…16 At present, palliative chemotherapy remains the main therapeutic approach used to treat advanced gastric cancer, but the response rates to combined chemotherapy range from approximately 26% to 47.9%. 13,17,18 In this study, 185 patients were subjected to 5-fluorouracil-based chemotherapy and the objective response rate of group A was 34.3%, which was similar to that in a previous study. 19 With the high incidence of lymph node metastasis and the lack of effective therapies, HIFU has been considered a strong candidate for treatment combined with chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…pFUS exposures similar to those employed in the present study have been used to non-invasively and nondestructively enhance the delivery of a variety of systemically administered agents in murine solid tumors including plasmid DNA (Dittmar et al, 2005), small molecules (Poff et al, 2008), nanoparticles (Frenkel et al, 2006), and monoclonal antibodies (Khaibullina et al, 2008). More recently, in a study in the murine skeletal muscle, the same exposures were shown to enhance the delivery of both systemically and locally administered nanoparticles (Hancock et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
“…As a result, temperature elevations may be just a few degrees Celsius (and hence non-destructive), allowing for more delicate, non-thermal mechanisms to occur (Frenkel, 2008). pFUS exposures have demonstrated the ability to noninvasively enhance the delivery of a variety of systemically administered agents to solid tumors, including small molecules (Poff et al, 2008), plasmid DNA (Dittmar et al, 2005), monoclonal antibodies (Khaibullina et al, 2008), and nanoparticles (Dittmar et al, 2005;Frenkel et al, 2006). More recently, these exposures were shown to enhance the distribution of locally administered nanoparticles in skeletal muscle (Hancock et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that pFUS exposure may alter vascular or cell membrane permeability to enhance drug delivery in tumors in animal models (Bednarski et al 1997, Nelson et al 2002, Dittmar et al 2005, Yuh et al 2005, Frenkel V et al 2006a, Hancock et al 2009and Chen et al 2010. Enhancement of drug delivery to the tumor target by pFUS exposures and its effect on tumor growth inhibition in vivo has been reported by other investigators (Dittmar et al 2005, Dromi et al 2007and Poff et al 2008.…”
Section: Introductionmentioning
confidence: 88%